(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
98 samples from various clinical sources (burns, wounds, urine, blood, and sputum) were gathered for this investigation from hospitals in Baghdad. Following microscopic and biochemical analysis, 52 Pseudomonas aeruginosa isolates were discovered. The microtiter plate method was used to determine if the bacterial isolates could create biofilm. The outcomes revealed that 80% of the detaches could shape biofilm to varying degrees, with 28.9% of the disengages framing frail biofilm, 24.4% medium biofilm, and 26.7% solid biofilm. Acetic acid shown anti-biological activity, hence a progressive effect of the acid (0.009 – 2.5 %) on biofilm formation was also investigated.